Rancangan Penurunan Tingkat Kecacatan Produk Velg dengan Filosofi Six Sigma di PT. X - Alfian Hernawan; Jani Rahardjo (Jurnal Titra, 2021)
Company X is a company engaged in the manufacture of wheels, especially wheels for cars. This research was conducted to reduce the percentage of defects in the production process of wheels at company X. The most common defects in the wheels include leaks on the wheels, the wheels are porous, and the edges of the wheels are not flat. The percentage of defective products on wheels in 2019 was 7.97%. The defect occurs when the wheel manufacturing process takes place so that the wheels may experience defects due to errors in the wheel production process. The fix for the problems that occur in this study uses the six sigma philosophy. In the Six Sigma philosophy, there are methods used to solve problems, namely DMAIC (Define, Measure, Analyze, Improve, Control). The DMAIC method helps research by finding out the root problems that occur in the wheel production process. The tool used to find the root of the problem is a fishbone diagram. The results of the fishbone diagram show defects that occur up to the deepest roots so that the main cause of the defect can be identified. The proposed improvement is then determined using the 5 why analysis method. The prioritized design of improvement proposals to be carried out is to supervise the operator, give a dividing mark between the operator and the printing equipment, use a temperature gauge, and provide training for operators.